Community Participation in Non-communicable Disease Integrated Counselling Unit - Adnani, Hariza; Nurjannah, Nurjannah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
This study discusses the internal factors of non-communicable disease integrated counseling unit (NCD Posbindu) implementation with community participation in NCD Posbindu village districts Wirobrajan, Yogyakarta. The design of this study was a cross-sectional study with a population of 58 people. Sampling using purposive sampling technique obtained 46 people. Bivariate data analysis uses the Kendall Tau test. The study notes a relation of knowledge to community participation with the results of significant value P-value of 0.002 0.05. The Perceptions related to community participation get a significant P-value of 0.001 0.05. The motivation was related to community participation with a significant P-value of 0.000 0.05. Multivariate data analysis uses simple linear regression. The study notes that from 46 samples, F value F table (10.599 = 2.83). There is the influence of knowledge, perception, and motivation towards the NCD Posbindu implementation by community participation. The independent variables where the dominant influence is motivated by the largest value of Standardized Beta Coefficient is equal to 0.362.